Emergent Communication: The evolution of simplistic machines using different communication types - Karpul, Alexander (Department of Computer Science, 2014)
The methods of transmitting information may be divided as follows: direct; and, indirect. The âdirectâ method occurs when a creature transmits a signal that other creatures in its local environment can receive. Word of mouth advertising is a form of direct communication. âIndirectâ communication relays a message through the environment. This type of communication is known as stigmergy. Both word of mouth communication and stigmergy require the existence of groups of communicators. It is, however, difficult to analyse a very large number of local interactions that occur in group behaviour. A global phenomenon known as âemergenceâ arises from such behaviour. The phrase ââthe whole is greater than the sum of its partsâ normally describes emergence. In this research, we investigate how the two methods of communicating, direct and indirect (including a combination of these), result in emergent behaviour. In order to establish this outcome we employed the use of agent-based software in which we designed groups of agents to evolve over generations in response to specific situations. The manner in which these agent groups evolve is by a genetic algorithm. This is based on the consumption and collection of resources from the environment - a metric for gauging how well the population performs as a whole. For the purpose of this dissertation, we measure and examine the performance of four styles of the two methods of communication: No Communication, Word of Mouth, Stigmergic and Both (a combination of direct and indirect). We observe the fitness arising through successive generations of agents for each of the four styles and compare the results. The âNo Communicationâ style is markedly the worst performer and is âthe sum of the partsâ in terms of the definition of emergence. The âWord of Mouthâ style is marginally below the best performer but is rated well above that of âNo Communicationâ. The âStigmergicâ style is only the third best performer. Combining the direct and indirect methods yields the best result for the âBothâ style. All the communicating categories, considered âthe wholeâ in terms of the definition for emergence, outperform the âNo Communicationâ style. This demonstrates that emergence occurs when using these communication methods in groups. Keywords: Communication, Emergence, Genetic Algorithms, Group Behaviour